Obtežena povprečja in paradoks prijateljstva - Ferčec, Brigita (Obzornik za matematiko in fiziko, 2016)
The paper describes an iteresting phenomenon which appears in many areas of life and is known as the friendship paradox. The latter is connected with a special type of weighted averages in mathematics. Thus, in the beginning the concept of weighted averages is described as well as its applications and a mathematical interpretation. The last part describes the friendship paradox as it appears in the context of social networks. The connection with weighted averages and connections with some other areas are stated.
Keywords: družabna omrežja; friendship paradox; paradoks prijateljstva; social networks